Gestational protein restriction delays prostate morphogenesis in male rats - Pinho, Cristiane F. [UNESP]; Ribeiro, Mariana A. [UNESP]; Rinaldi, Jaqueline C. [UNESP]; Felisbino, Sergio L. [UNESP]; Pinheiro, Patricia F. [UNESP]; Domeniconi, Raquel F. [UNESP]; Fochi, Ricardo A.; Boer, Patricia A. [UNESP]; Scarano, Wellerson R. [UNESP] (Csiro Publishing, 2014)
Maternal malnutrition due to a low-protein diet is associated with functional disorders in adulthood, which may be related to embryonic development failures. The effects of gestational protein restriction on prostate morphogenesis in male offspring were investigated. Pregnant rat dams were divided into normoprotein (NP; fed a normal diet containing 17% protein) and hypoprotein (LP; fed a diet containing 6% protein) groups. On the day of birth (PND1), anogenital distance and bodyweight were measured in male pups. Seven males per experimental group (one male per litter) were killed, and the pelvic urethra was evaluated. LP offspring showed a significant reduction in bodyweight and anogenital distance on PND1. On three-dimensional reconstruction of the prostate, the number of prostatic buds was lower in LP than in NP males. Mesenchymal cells surrounding the buds were androgen-receptor positive, and the quantity and intensity of nucleus immunoreactivity was decreased in LP. The proliferation index was lower in LP than in NP prostatic buds. Immunoreactivity for -actin in mesenchymal cells and that for epidermal growth factor receptor in epithelial cells was higher in NP than in LP. Our findings demonstrate that maternal protein restriction delays prostatic morphogenesis, probably because of considerable disruption in the epithelium-mesenchyme interaction.
Keywords: epithelium-mesenchyme interaction; fetal programming